ANALISIS POTENSI PRODUKSI SKUALENA DARI BAKTERI V. SALARIUS 19.PP.SC1.6. DALAM MEDIA ZOBELL MARINE BROTH - Puteri Ariffia, Priyanka
Nutraceutical products are one of the types of products that are highly sought after by the market, in line with the increasing awareness of the importance of health among the public. Squalene is one of the nutraceutical products that has many benefits for humans, such as being an antioxidant, skincare additive, anti-infective agent, detoxification agent, and drug delivery agent. The main producer of squalene is sharks, which are known to be rare animals and threatened with extinction if used for squalene production. Therefore, an alternative production of squalene from other sustainable biological sources is needed. Virgibacillus salarius is one of the biological resources that can serve as an alternative producer of squalene. This study uses Virgibacillus salarius strain 19.PP.Sc1.6 as a sample to investigate its potential as a squalene producer and determine kinetic parameters such as growth pattern, substrate utilization pattern, specific growth rate (?), generation time (Gt), and substrate utilization kinetic parameter (Yx/s). In this study, V. salarius 19.PP.Sc1.6 was cultivated in Zobell Marine Broth (ZB) medium for 96 hours at a temperature of 30°C, 130 rpm, pH 7.6, initial inoculum of 107 cells (10% (v/v)), 2% NaCl, and a working volume of 500 mL with sampling taken every 12 hours. The results of this study showed that V. salarius 19.PP.Sc1.6 entered the stationary phase at 48 hours with specific growth rate (?) and generation time (Gt) values of 2.96±0.20 hours and 0.203±0.004 hours^-1, respectively. It was also found that the biomass of V. salarius 19.PP.Sc1.6 continued to increase along with the decrease in sucrose and fructose concentrations, with parameter values of Yx/s for sucrose being 0.0428 (g/g) and for fructose being 0.0037 (g/g). V. salarius 19.PP.Sc1.6 was able to produce squalene with a yield of 0.342 mg/L at the 96- hour sampling time using liquid-liquid extraction method.